Egnatia Odos! 60 Miles of Mountainous Road Tunnels in Northern Greece, Europe - N. Kazilis; G. Aggistalis; N. Rachaniotis; S. Raptopoulos; C. Rawlings; R. Game; M. Knights (Society for Mining, Metallurgy & Exploration, 2005)
The Egnatia Odos (Odos meaning road) is one of Greece’s largest ever highway construction projects and one of Europe’s most important. The Highway will assist in the connection of the Greek Ionian/Adriatic Coast with Turkey and the Black Sea reviving an historic Roman alignment “Via Egnatia” connecting Rome to Constantinople (now Istanbul). There are 74 twin tunnels (60 bored and 14 cut-and-cover) with lengths ranging from 160 m (175 yd) to 4,600 m (5,031 yd) and 100 m (109 yd) to 270 m (295 yd),respectively. The complex geology and resulting physical geography have had a major influence on both the design and construction of these tunnels. This paper describes the management, design and construction challenges of these numerous tunnels.